2021
DOI: 10.1371/journal.pone.0248972
|View full text |Cite
|
Sign up to set email alerts
|

Readmission within three months after inpatient geriatric care—Incidence, diagnosis and associated factors in a Swedish cohort

Abstract: Introduction Readmissions are very costly, in monetary terms but also for the individual patient’s safety and health. Only by understanding the reasons and drivers of readmissions, it is possible to ensure quality of care and improve the situation. The aim of this study was to assess inpatient readmissions during the first three months after discharge from geriatric inpatient care regarding main diagnosis and frequency of readmission. Furthermore, the aim was to analyze association between readmission and pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Polypharmacy is known to be associated with various negative outcomes including declined physical, cognitive, and emotional capabilities as well as hospitalization [ 5 , 27 ]. Several studies have correlated polypharmacy with hospital readmission among older patients [ 3 , 6 , 7 ]. However, this was not the case in our study, in which neither polypharmacy nor hyperpolypharmacy was significantly related to hospital readmission.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Polypharmacy is known to be associated with various negative outcomes including declined physical, cognitive, and emotional capabilities as well as hospitalization [ 5 , 27 ]. Several studies have correlated polypharmacy with hospital readmission among older patients [ 3 , 6 , 7 ]. However, this was not the case in our study, in which neither polypharmacy nor hyperpolypharmacy was significantly related to hospital readmission.…”
Section: Discussionmentioning
confidence: 99%
“…A high hospital readmission rate among older population might be due to many factors. One of them is the individual’s multiple diseases progression as well as deterioration of their health status that make them more prone to seek treatment [ 3 ]. Other than that, demographic factors were also found to significantly contribute to readmission.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Swedish study of a cohort of older people showed how the trajectories of the patients in various clusters changed over a 12-year period 18 . This study is part of a larger project with the aim to analyse reasons and drivers for readmission after discharge from geriatric care 23,24 . Due to the prevalence of multimorbidity in elderly populations, the phenomenon of multimorbidity needs to be explored and analysed more rigorously, contributing to a profound ground for analyses of reasons for readmission.…”
Section: Patients In Geriatric Carementioning
confidence: 99%